Ireland and the Global Financial Crisis: Growth, Volatility and Financial Development - Byrne, Julie (Statistical and Social Inquiry Society of Ireland, 2010)
I examine the impact that a decline in financial development could have on Ireland.s growth performance in light of the current credit crisis. A Markov-switching model with time-varying transition probabilities is applied to Irish data to examine the link between financial development and growth. In the model, the growth rate moves discretely between two regimes; one characterised by high average growth and low volatility, the other a more volatile low growth regime. Inferences are then made by estimating how long the country can be expected to remain in a slow growth regime, at given levels of financial development. The results show that higher levels of financial development correspond to spending more time in the higher growth regime. Furthermore, it is shown that the expected duration of remaining in the slow growth regime increases as financial development falls. This analysis takes into account the fact that the dynamics of output following a shock such as a financial crisis differs significantly from the dynamics of output during more stable time periods by taking a non-linear approach.
(read before the Society, 25 March 2010)
Keywords: financial development; econometrics; data modelling; 314.15